Castillón, E.E. & Quintanilla, J.A.V. (2016) A new species of Dalea (Fabaceae, Faboideae) from Jalisco, México. Phytotaxa 246 (1): 90–92. - Castillón, Eduardo Estrada; Quintanilla, José Angel Villarreal (Phytotaxa, 2016)
N/A